FENOMENA KERIS TERHADAP KEHIDUPAN SOSIAL MASYARAKAT JAWA - Darmojo, Kuntadi Wasi (Institut Seni Indoensia Surakarta, 2015)
Keris is a work of art that have aesthetic value and the value of philosophy that can be used as guidance and spectacle, the social life of Java. Kris culture in Indonesia has been known since the 10th century and has continued until now. Kris as objects tradition that has been handed down and there is a change in character bit by bit according the demands of time or the king ( ruler ). When seen his form dagger is an art that has achieved a high level of sophistication and qualifies it has a symbolic meaning, so that the existence of a dagger in the Java community, by most people had believed that the order of the social life of a man is not considered perfect in the achievement of social value if it does not have a keris. The existence of a dagger function in social life has undergone many shifts according to the demands of the times, even in the social and cultural life in contemporary times functions in supporting community has emerged an interesting phenomenon. Kris as non material Cultural Heritage (intangible ) has received recognition from UNESCO as it has among other things: the historical value, aesthetic, social function, philosophy , symbols and mystical .Â Keywords: Culture, Keris, Function and SocietyÂ